Tunable longitudinal modes in extended silver nanoparticle assemblies - Bayram, Serene S.; Lindfors, Klas; Blum, Amy Szuchmacher (Beilstein Journal of Nanotechnology, 2016)
Nanostructured materials with tunable properties are of great interest for a wide range of applications. The self-assembly of simple nanoparticle building blocks could provide an inexpensive means to achieve this goal. Here, we generate extended anisotropic silver nanoparticle assemblies in solution using controlled amounts of one of three inexpensive, widely available, and environmentally benign short ditopic ligands: cysteamine, dithiothreitol and cysteine in aqueous solution. The self-assembly of our extended structures is enforced by hydrogen bonding. Varying the ligand concentration modulates the extent and density of these unprecedented anisotropic structures. Our results show a correlation between the chain nature of the assembly and the generation of spectral anisotropy. Deuterating the ligand further enhances the anisotropic signal by triggering more compact aggregates and reveals the importance of solvent interactions in assembly size and morphology. Spectral and morphological evolutions of the AgNPs assemblies are followed via UV–visible spectroscopy and transmission electron microscopy (TEM). Spectroscopic measurements are compared to calculations of the absorption spectra of randomly assembled silver chains and aggregates based on the discrete dipole approximation. The models support the experimental findings and reveal the importance of aggregate size and shape as well as particle polarizability in the plasmon coupling between nanoparticles.
Keywords: plasmon coupling; self-assembly; silver nanoparticles